Evidence for significant climate impacts in monsoonal Asia at 8.2 ka from multiple proxies and model simulations - Morill, Carrie (author); Wagner, Amy (author); Otto-Bliesner, Bette (author); Rosenbloom, Nan (author) (2011)
Given the likelihood of future reductions in the strength of the Atlantic Meridional Overturning Circulation (AMOC), it is important to document how changes in the AMOC have altered climate patterns in the past and to assess the skill of coupled climate models in reproducing these teleconnections. Of past abrupt changes in the AMOC, the 8.2 ka event provides a particularly useful case study because its duration, magnitude of AMOC reduction and background climate state are closest to conditions expected in the future. In this research, we present an expanded proxy synthesis of the 8.2 ka event in monsoonal Asia, including new high-resolution lake and bog records, more sites from the East Asia monsoon region and proxies of winter monsoon strength. We compare proxy evidence with a new simulation of the 8.2 ka event using the Community Climate System Model version 3 (CCSM3) and prescribing North Atlantic freshwater forcing according to the latest reconstructions. We fi nd clear and objectively-determined evidence for 8.2 ka climate anomalies at nearly all of the fourteen proxy sites, emphasizing the strong and widespread impacts of the event in monsoonal Asia during both summer and winter seasons. The model simulation corroborates that these anomalies, described generally as a weakening of the summer monsoon and strengthening of the winter monsoon, were likely caused by a reduction of the AMOC. Examination of regional anomalies in East Asia reveals some spatial heterogeneity, however, that in the model simulation is caused by contraction of the seasonal migration of the subtropical monsoon front. The duration of climate anomalies at 8.2 ka in monsoonal Asia, both in proxy records and the model simulation, generally matches the duration of the event in Greenland ice core δ¹⁸O, further supporting a tight connection to the North Atlantic.